2012
DOI: 10.1590/s0102-695x2012005000069
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of volatile composition of Laurencia dendroidea by gas chromatography-mass spectrometry

Abstract: Abstract:In this study we report the characterization of the volatile compounds of Laurencia dendroidea. Solvent extracts (dichloromethane and methanol), hydrodistillation extracts and headspace solid-phase microextraction samples were obtained and analyzed by GC-MS. Forty-six volatile components were identifi ed in L. dendroidea, among them hydrocarbons, alcohols, phenols, aldehydes, ketones, acids, esters and terpenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Wang et al [5] analysed the VOCs of three red seaweeds ( Grateloupia filicina , Polysiphonia senticulosa and Callithamnion corymbosum ) from the Yellow Sea of China and found that the main VOCs were aldehydes, ketones, alkenes and alcohols. As previous reported by Gressler et al [34] , algae-derived compounds, only 46 metabolites were identified as terpenes, alcohols, acids, esters, ketones, and hydrocarbons detected.…”
Section: Resultssupporting
confidence: 77%
“…Wang et al [5] analysed the VOCs of three red seaweeds ( Grateloupia filicina , Polysiphonia senticulosa and Callithamnion corymbosum ) from the Yellow Sea of China and found that the main VOCs were aldehydes, ketones, alkenes and alcohols. As previous reported by Gressler et al [34] , algae-derived compounds, only 46 metabolites were identified as terpenes, alcohols, acids, esters, ketones, and hydrocarbons detected.…”
Section: Resultssupporting
confidence: 77%
“…Additionally, the biopharmaceutical and nutritional values of these genera related to life expectancy through dietary intake have been considered. So, it could be expected the risk of some chronic diseases clearly be reduced through the consummation of these types of seaweeds ( 13 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, insight on the metabolite chemistry of different Laurencia complex species may prove to be a valuable chemotaxonomic tool at the generic or species level. To the best of our knowledge, most of these approaches have been carried out using different chromatographic techniques coupled to MS detectors , but they are still few and none of them have used CE.…”
Section: Introductionmentioning
confidence: 99%